Platform Organisations in Social Innovation: A Lot of Old Wine in a Bottle - Busacca, Maurizio (PARTECIPAZIONE E CONFLITTO, 2019)
The article investigates the influence of platform ideas, schemes, and production models outside the high-tech industry. To do this, it studies the organisational models of seven social innovation initiatives active in Italy in different sectors and promoted by different actors. The initiatives, even if non-high-tech, can be put in order as platform organisations because they host interactions between a variety of organisations and people, differently arranged with respect to them and largely autonomous and heterogeneous in terms of their interests, social networks, and purposes. The main purpose of this research has three sub-objectives. The first is to observe the development of extensive ’platformisation’ processes of production systems. The second is to deepen trends in the high-tech sector through the observation of the non-high-tech sector. Finally, to create useful and usable knowledge to help political parties, trade unions, associations and governments plan solutions to protect workers of the platforms. Using a critical approach, the article reveals that these organisations are less innovative than their supporters report for three reasons. Firstly, because the concept of community is abused to describe these organisations, which present themselves mainly as coalitions or networks because their members lack a common sense of membership; secondly, because the research downsizes the presence of prosumers and peer-to-peer production and describes production and consumption processes that take place at separate times and in which peer production is only a marginal part of the production reality. In the end, because of these organisations work thanks to the job of a small group of people with high cognitive skills and relational capital that trigger production by activating, managing and capitalising a small crowd of workers.